Invest the city by doing businesses: Geographies of migrant entrepreneurs in the center of Athens - Polyzou, Iris (The Greek Review of Social Research, 2020)
The aim of this paper is to describe the geographies of migrant entrepreneurship in Athens from the scale of the municipality to the street level. The purpose of this multiscalar approach is to explore two main issues: firstly, to investigate the location of enterprises by nationality at the scale of the municipality and, secondly, to analyse the sociospatial practices in starting up and running a business within the particular urban context of three areas of Athens, the years following the economic recession. The paper is based on a research program conducted at the French School at Athens from 2015 to 2017.